Conductivity-Dependent Strain Response of Carbon Nanotube Treated Bacterial Nanocellulose. (12th February 2013) - Farjana, S.; Toomadj, F.; Lundgren, P.; Sanz-Velasco, A.; Naboka, O.; Enoksson, P.
Abstract : This paper reports the strain sensitivity of flexible, electrically conductive, and nanostructured cellulose which was prepared by modification of bacterial cellulose with double-walled carbon nanotubes (DWCNTs) and multiwalled carbon nanotubes (MWCNTs). The electrical conductivity depends on the modifying agent and its dispersion process. The conductivity of the samples obtained from bacterial cellulose (BNC) pellicles modified with DWCNT was in the range from 0.034 S·cm −1 to 0.39 S·cm −1, and for BNC pellicles modified with MWCNTs it was from 0.12 S·cm −1 to 1.6 S·cm −1 . The strain-induced electromechanical response, resistance versus strain, was monitored during the application of tensile force in order to study the sensitivity of the modified nanocellulose. A maximum gauge factor of 252 was found from the highest conductive sample treated by MWCNT. It has been observed that the sensitivity of the sample depends on the conductivity of the modified cellulose.